Methods of working on the active grammatical minimum - Abduvoitov Ravshanbek (Euro Asian Journal Publishing, 2024)
Remember that active grammar is a key aspect of effective communication in many languages, including English. By regularly practicing and applying active grammar principles, you can improve your language skills and express yourself more confidently.
Keywords: Ideas; grammar books; voice; language